Variability of the antitubercular activity of Ampalaya (Momordica charantia L.) from selected provinces in Luzon, Philippines - Panlilio, Bella G.; Franzblau, Scott G.; Aguinaldo, Alicia M. (2007)
An earlier study had found that the crude alcoholic extract of the leaves of M. charantia L. inhibited the growth of Mycobacterium tuberculosis H 37Rv by 94% at 100 mg mL-1, and by 100% at 1000 mg mL -1. In our study, the crude alcoholic extracts of M. charantia were tested, using Microplate Alamar Blue Assay, to determine the inhibitory activity of M. charantia against M. tuberculosis H37Rv. Based on the results, M. charantia leaves generally showed the highest inhibitory activity (48-100% at 100 mg mL-1). Among the M. charantia species collected from five provinces in Luzon, Philippines, the leaves, fruits and stems of the species from the Bicol Region showed the highest percent inhibition (100%) against M. tuberculosis H37Rv. The antitubercular activity of the leaves of the cultivated variety was higher (99%) than that of the wild variety (90%) whereas the antitubercular activity of the fruits of wild M. charantia (90%) was higher than that of the cultivated variety (81%). The difference between the antitubercular activity of the young (99%) and the mature (98%) leaves of cultivated M. charantia was minimal.
Keywords: Ampalaya (Vegetable)